2023
DOI: 10.7717/peerj.16239
|View full text |Cite
|
Sign up to set email alerts
|

A review on the relationship between Arachidonic acid 15-Lipoxygenase (ALOX15) and diabetes mellitus

Kaiying He,
Xiaochun Zhou,
Hongxuan Du
et al.

Abstract: Arachidonic acid 15-lipoxygenase (ALOX15), as one of the lipoxygenase family, is mainly responsible for catalyzing the oxidation of various fatty acids to produce a variety of lipid components, contributing to the pathophysiological processes of various immune and inflammatory diseases. Studies have shown that ALOX15 and its related products are widely distributed in human tissues and related to multiple diseases such as liver, cardiovascular, cerebrovascular diseases, diabetes mellitus and other diseases. Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 156 publications
0
3
0
Order By: Relevance
“…It has been hypothesized that ALOX15 inhibitors have the potential to be used as treatments for airway inflammatory diseases, including asthma. ALOX15 and its metabolites have also been implicated in the pathology and mechanism of T2DM, which may be related to the effect of ALOX15 on islet cell and macrophage functions, (He et al, 2023), as well as in serious complications that arise from the disease, such as diabetic retinopathy, peripheral neuropathy, and nephropathy (Singh and Rao, 2019). This implies that ALOX15 inhibitors may also be explored as a possible treatment for T2DM and/or its complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been hypothesized that ALOX15 inhibitors have the potential to be used as treatments for airway inflammatory diseases, including asthma. ALOX15 and its metabolites have also been implicated in the pathology and mechanism of T2DM, which may be related to the effect of ALOX15 on islet cell and macrophage functions, (He et al, 2023), as well as in serious complications that arise from the disease, such as diabetic retinopathy, peripheral neuropathy, and nephropathy (Singh and Rao, 2019). This implies that ALOX15 inhibitors may also be explored as a possible treatment for T2DM and/or its complications.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review (Xu et al, 2021), it was mentioned that human arachidonic acid 15-lipoxygenase (ALOX15) inhibitors have the potential to be used as treatments for airway inflammatory diseases, including asthma. ALOX15 and its metabolites have been suggested to also play a role in T2DM and the complications that arise from it (Singh and Rao, 2019;He et al, 2023), implying that ALOX15 inhibitors may be explored as a possible treatment for T2DM and/or its complications. Several compounds and plant extracts that inhibit α-glucosidase or ALOX15 have already been studied (Kumar et al, 2011;Sadeghian and Jabbari, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that ALOX15 and its related products are expressed at high levels in many pathological human tissues and organs, which consequently cause in ammation, oxidative stress and iron death [30]. ALOX15 has a proin ammatory effect, and it has been found that ALOX15 metabolites can stimulate the expression of IL-6 and TNF-α in a dose-dependent manner [31], and it promotes the production of in ammatory factors through the activation of mitogen-activated protein kinase, protein kinase C and other pathways [32]. ALOX 15 has also been associated with oxidative stimulation in humans.…”
Section: Discussionmentioning
confidence: 99%